CAN AUDIT QUALITY MODERATE THE FRAUD HEXAGON ON FINANCIAL REPORT FRAUD IN CONSUMER CYCLICALS SECTOR? - Hakim, Mohamad Zulman; Dewi Rachmania; Galang Reza Firdaus Budiutomo; Yola Dyfa Meisari; Helen Retno Wulandari; Thorik Satria Ilmi (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
The goal of the present study is to collect empirical evidence regarding the Factors in The Hexagon Theory of Fraud that. able detect fraudulent financial statements The case study of the Consumer Cyclical Sector on the IDX in the range of 2020-2022 is used in testing the Fraud Score model. In this analysis, 89 Consumer Cyclicals companies serve as samples, purposeful sampling is used to select samples, Fraud with financial statements (KLK) is a dependent factor in this investigation.The independent variables used are financial targets, financial stability, external pressure, CEO education, political connections, state-owned enterprises, external auditors, rationalization, and CEO duality. Eviews version 13 testing software was used for data analysis of. analysis of multiple linear regression . Audit quality is able to moderate the impact of ROA, ACHANGE, LEV, RAS and Ceodual on the potential for falsified accounts payable. Although audit quality cannot lessen the impact of CEO education, political connections, SOE, government projects, on indications of fraud on financial statements.